I Am Telling This to No One But You:: Private Voice, Passing, and the Private Sphere in Margaret Atwood's Alias Grâce - Lovelady, Stephanie (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 1999)
Margaret Atwood's Alias Grace brims with references to the act of narration. Private and public narration intersect in Grace's tale, which cannot be said to be truly private or public, but which moves along a continuum between these two poles. In three realms, narrative transmission, her perception of her ethnic identity, and her adoption of gender roles, there is a movement away from the public toward the private. The mixture of public and private voice in Grace's narration is not merely a curiosity, but demonstrates Grace's unfulfilled needs for privacy and intimacy.